Upaya Meningkatkan Kesehatan Mental Di Era Revolusi Industri 4.0 Melalui Psikoedukasi Dan Pendampingan Membangun Konsep Diri Positif Pada Siswa SMP - Dewi Anggraini; Amalia Juniarly; Dini Darmayanti; Rifda Alda Ufaira (Altifani Journal: International Journal of Community Engagement, 2026)
The main theme of this community service activity is the effort to improve mental health in the Era 4.0 through psychoeducation and mentoring to build a positive self-concept among junior high school students. The Industrial Revolution 4.0 era has brought significant changes to the social and emotional lives of adolescents, especially in the use of gadgets, where adolescents can easily access social media, the internet, and digital devices, which in turn can influence how adolescents view themselves, compare themselves to others, and build social relationships. This, of course, also impacts the mental health of school-age adolescents. Therefore, one effort that can be made is to foster an understanding of self-concept among adolescents. Self-concept is a self-evaluation based on one's life, appearance, academics, and other factors. This activity was carried out by providing psychoeducation as well as mentoring through group counseling. The results of this activity have provided students with insights related to positive self-concept, as can be seen from the pre- and post-test results in which the average score increased by 0.625. In addition, counseling activities have enabled students to become more confident and adaptive to technology. It is hoped that this activity will be sustained within the school guidance counseling program and involve guidance counseling teachers.